TRADITION MODERATION RELIGIOUS AS ISLAMIC BOARDING SCHOOL CULTURE: COMPARATIVE STUDY IN REGENCY SIMALUNGUN - Sopian Lubis; Syamsu Nahar; Dedi Masri (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
Study This aim analyze How moderation religious live and reproduce as a pesantren culture through system education morals. In the middle increasing polarization socio-religious, Islamic boarding schools viewed own role strategic in build tradition inclusive and balanced religiosity. However, studies that examine moderation religious as an internalized culture in system education Islamic boarding school in a way comparative Still limited. Research This use approach qualitative multi-site with technique data collection in the form of interview in-depth, observation participatory, and study documentation on several Islamic boarding schools in the Regency Simalungun. Data analysis was carried out through the interactive model of Miles, Huberman, and Saldaña with stages data condensation, data presentation, and retrieval conclusion cross- site (cross-case analysis). Research result show that moderation religion in Islamic boarding schools No taught in a way normative-doctrinal only, but reproduced as a culture through exemplary behavior of kyai and ustaz, system 24-hour education, habituation discipline religious, deliberation, and respect to differences. In terms of comparative, found pattern general in the form of integration mark i'tidal (justice), tawazun (balance), and tasamuh (tolerance) in practice daily life santri, even though there is variations in implementation strategies influenced by character leadership and context the institutions of each Islamic boarding school. Findings This strengthen that education morals play a role as the main medium internalization mark moderation so that form tradition inclusive and adaptive religiosity in context plural society. Research This contribute to the development of conceptual models moderation religious as an educational culture Islamic boarding school.